FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN MEMBUANG SAMPAH DI LINGKUNGAN IV KELURAHAN HELVETIA KECAMATAN MEDAN HELVETIA TAHUN 2017 - Napis Alfikri; Wisnu Hidayat; Vierto Irennius Girsang (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Garbage is the consequence human activity in the form of disposal or waste. There are 2000 tons of garbage per day in Medan, and most of the garbage which comes from people’s homes and is produced by housewives reaches to 1,500 to 1,600 tons per day. which is caused by several factors that are predisposition, enabler and amplifier. The objective of the research was to find out some factors which were correlated with the behavior of action throwing garbage at Lingkungan IV, Kelurahan Helvetia, Medan Helvetia, in 2017. The population was178 people, and 123 of them were used as the samples. The research used observational analytic method with cross sectional design. The data were analyzed by using univariate anaslysis, bivariate analysis, and multivariate analysis. The result of the research showed that there was the correlation of knowledge (p-value = <0.001), attitude (p-value = 0.004), education (p-value = <0.001), availability of facility (p-value = <0.001), socialization of health care providers (p-value = <0.001), and knowledge about perda no 6 year 2015 (p-value = <0.004) of throwing garbage. The variable which had the most dominant correlation with of throwing garbage was knowledge which 8.6 times of the possibility to be a good behavior in throwing garbage compared with those who had bad knowledge. It is recommended that the Government do regular evaluation and promote environmental health by making public figures participate in good behavior of throwing garbage.Keywords: Predisposition, Enabling, Enforcing, Action Throwing Garbage